Uwarunkowania rozwoju klastrów jako narzędzia poprawy regionalnej efektywności działania - Chojnacki, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
"Clusters" mean firms' conglomerations dealing with production in one or similar branches with mutual informal dependencies and relations. Their amalgamation is based upon theoretical assumption - a common target influencing co-operation and competition among them, what stimulates innovativeness and development. Clusters bring profits both on an individual regional and on a global scale. Among them are: multidirectional regional development, regional infrastructure development, lower cost of development supporting, more comprehensive development than in the situation of investing in concrete economy branches. The important advantage is reducing unemployment thus influencing higher living standard in region. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 46-56